DARWINS GEMMULES AND ADAPTATION - Ibraimov, Abyt (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
Currently the origin of new adaptive forms, new body plans or species is associated with mutation of the gene (genes). The idea of biological variation is usually associated with the existence of the gene and the generation of form in biology is the result of the differential regulation of developmental genes. Without challenging the merits of such an approach, we offer, to revise the old hypothesis of Darwins gemmules, based in his theory of pangenesis. The fact is that the possibility of origination of complex adaptive forms only on the basis of random mutations at the genelevel is not proved yet. Darwin supposed that gemmules are the material sources of biological variation and they appear in response to the external environment. In recent years the data of new sources of biological variability were received (except for random mutations), based on which the new adaptive forms can appear. It is considered that evolution is a very slow process and therefore it cannot be observed directly in Nature. However, its turned out that sometimes under the effect of external factors evolutionary processes can dramatically accelerate, as has happened in the case of Anoliscarolinens living on Islands off the Florida coast. We suppose that the case of anoles provides scientists with a rare opportunity to test experimentally the hypothesis of Darwins gemmules.